Multiple case study analysis - Stake, Robert E. (The Guilford Press, 2006)
Examining situational complexity is a vital part of social and behavio ral science research. This engaging text provides an effective process for studying multiple cases–such as sets of teachers, staff developme nt sessions, or clinics operating in different locations–within one co mplex program. The process also can be used to investigate broadly occ urring phenomena without programmatic links, such as leadership or sib ling rivalry. Readers learn to design, analyze, and report studies tha t balance common issues across the group of cases with the unique feat ures and context of each case. Three actual case reports from a transn ational early childhood program illustrate the author's approach, and helpful reproducible worksheets facilitate multicase recording and ana lysis.
Keywords: Case method; Cross-cultural studies; Education; Europe; Eastern; Research Methodology; Step by Step (Program)